2013
DOI: 10.1093/mnras/stt2283
|View full text |Cite
|
Sign up to set email alerts
|

Sejong Open Cluster Survey (SOS) – II. IC 1848 cluster in the H ii region W5 West

Abstract: IC 1848 is one of the young open clusters in the giant star forming Cas OB6 association. Several interesting aspects relating to star formation processes in giant star forming regions attracted us to study the initial mass function (IMF), star formation mode, and properties of pre-main sequence stars (PMS). A U BV I and Hα photometric study of the young open cluster IC 1848 was conducted as part of the "Sejong Open cluster Survey" (SOS). We have selected 105 early-type members from photometric diagrams. Their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 87 publications
6
39
0
Order By: Relevance
“…These relations have been successfully used to determine the R V of several young open clusters. The color excess ratios of several young open clusters have been well fitted to a single line with a normal R V (Kook et al 2010;Lim et al 2011;Sung et al 2013a;Lim et al 2014aLim et al ,b, 2015a. However the color excess ratios of some extremely young open clusters are best fitted by a combination of two lines with different slopes, which means that two different media with different extinction properties exist in the line-of-sight, i.e.…”
Section: Reddening Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…These relations have been successfully used to determine the R V of several young open clusters. The color excess ratios of several young open clusters have been well fitted to a single line with a normal R V (Kook et al 2010;Lim et al 2011;Sung et al 2013a;Lim et al 2014aLim et al ,b, 2015a. However the color excess ratios of some extremely young open clusters are best fitted by a combination of two lines with different slopes, which means that two different media with different extinction properties exist in the line-of-sight, i.e.…”
Section: Reddening Lawmentioning
confidence: 99%
“…Currently, two stellar evolution models of massive stars with stellar rotation are used in the mass and age estimate of massive stars, and these are compared in Sung et al (2013a). For consistency with the mass and age scale of massive stars with previous studies of our group (Hur et al 2012;Sung et al 2013a;Lim et al 2014aLim et al ,b, 2015aHur et al 2015), the age and mass of massive stars are determined using the stellar evolution models of Ekström et al (2012).…”
Section: Age and The Initial Mass Function Of Ic 1805mentioning
confidence: 99%
“…The equivalent widths of spectral lines can be underestimated by excess continuum emission due to mass accretion activity (Calvet & Gullbring 1998;Lim et al 2014a ) were measured by integrating the observed emission lines. In the case of the He I line, we computed the equivalent width of the line core within a narrow wavelength range of 0.7 Å to minimize the contribution of the error in the continuum level.…”
Section: The Effect Of Veiling On the LI L6708 Linementioning
confidence: 99%
“…The distance range of W5 in the literature is 1.7-2.3 kpc (Sharpless 1955;Johnson et al 1961;Ishida 1970;Georgelin & Georgelin 1976;Chauhan et al 2011). In this paper, we adopt the most recent value of 2.2 kpc for the open cluster IC1848 (Lim et al 2014) as the distance to SFO12 and its exciting stars in W5-W. Four O stars (BD +60 586 A, HD 237019, HD 17520 and HD 17505; Koenig et al 2008) are present in the W5-W and the main exciting star of the bright rim of SFO 12 is BD +60 586 A (O7V; Sota et al 2011), as seen in Figure 1. The projected distance between SFO 12 and the main exciting star is ∼4.4 pc.…”
Section: Introductionmentioning
confidence: 99%